Implementasi Metode Promethee untuk Penentuan Penyedia Layanan Hosting Terbaik di Indonesia - Ma’had Wicaksono; Andrianto Gusti Pradana (Repeater : Publikasi Teknik Informatika dan Jaringan, 2025)
Determining the best hosting service provider is a very important first step in starting a digital business. Mistakes in choosing a hosting service will have fatal consequences for the continuity and smooth running of a digital business. This research aims to select the best hosting service in the form of a Decision Support System (SPK). Determining the best hosting service provider is very important because hosting is one aspect that determines the success of an e-business. This research uses the PROMETHEE (Preference Ranking Organization Method for Enrichment Evaluation) method to determine the ranking of the best hosting service providers. The performance assessment of hosting service providers was carried out from January to April 2024. This research was carried out using data from 9 alternatives and 5 criteria which are crucial aspects in hosting services, namely, loading time, server uptime, number of downtimes, support and user friendliness. In this research, it was found that the hosting service provider Niagahoster was the first ranked alternative with a net flow value of 0.75.